STRATEGI PEMASARAN DIGITAL PADA USAHA BAWANG GORENG DALAM MENJALANKAN BISNIS DI ERA NEW NORMAL - Said, Syarifah Maihani SE.MM; Jamilah, Maryam; Malik, Abdul; Khairani, Cut; Kumita, Kumita; Zaki Yamani, Said Ahmad (RAMBIDEUN : Jurnal Pengabdian Kepada Masyarakat, 2022)
The implementation of this community service (PKM) is an effort to develop "fried onion" home business in developing its business through digital marketing so that the products can be accessed easily from home. The PKM team proposes to partners the skills to make good quality fried onions in terms of health and marketability and to equip them with knowledge to apply management systems of digital marketing to their business activities, good packaging and legal business permits. An issue that is no less important, which has received less attention from partners is the pollution of environmental cleanliness around the work area. The work area still has a dirt floor, the smoke from burning firewood is naturally discharged into the air (without being treated for emission reductions that endanger health and intelligence), and the ash area of ​​cooking residue is still left untreated, making it difficult for the cleaning process. As well as optimizing the multimedia platform to provide information and answer public complaints. The solution offered by the proposing team in solving partner problems is optimizing the use of the internet in conducting digital marketing and collaborating with online marketing application providers involving many people with digital interactions. It also requires good commitment and collaboration between the government, academia, financial institutions, and information technology companies to increase competitiveness.